What Role Does Patient Gratitude Play in the Relationship Between Relationship Quality and Patient Loyalty? - Huang, Chih-Hsuan (Inquiry, 2019)
The environment in health care organizations is becoming increasingly competitive. Therefore, to improve patient return rates, health care organizations need to examine how to enhance the physician-patient relationship. In particular, the role of patient gratitude on the physician-patient relationship in health care organizations is still ambiguous. The specific role of patient gratitude in the medical service industry needs to be identified. Therefore, this study aimed to investigate physician-patient interactions with reference to relationship marketing and to further understand the relationships among relationship quality, patient gratitude, and patient loyalty. The potential effects of patient gratitude on the physician-patient relationship were examined by testing mediation effect. The results demonstrated that patient gratitude had a notable effect on the association between relationship quality and patient loyalty. To improve the physician-patient relationship in the medical service industry, health care managements should not ignore the 3 relationship quality tactics perceived by patients, specially the role of the potential effect of patient gratitude on relational building.